2007
DOI: 10.1016/j.socscimed.2007.05.048
|View full text |Cite
|
Sign up to set email alerts
|

The association between contextual socioeconomic factors and prevalent asthma in a cohort of Southern California school children

Abstract: Spatial variation in childhood asthma and a recent increase in prevalence indicate that environmental factors play a significant role in the etiology of this important disease. Socioeconomic position (SEP) has been associated inversely and positively with childhood asthma. These contradictory results indicate a need for systematic research about SEP and asthma. Pathways have been suggested for effects of SEP on asthma at both the individual and community level. We examined the relationship of prevalent asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 70 publications
3
44
1
1
Order By: Relevance
“…These results are consistent with observations made by other authors. Most studies point out that children whose families are characterized by a low SES have respiratory system symptoms more frequently than bronchial asthma itself [7,14,15]. Unfortunately, the design of our study does not allow for more detailed explanation of the differences between SES and the incidence of respiratory disease.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with observations made by other authors. Most studies point out that children whose families are characterized by a low SES have respiratory system symptoms more frequently than bronchial asthma itself [7,14,15]. Unfortunately, the design of our study does not allow for more detailed explanation of the differences between SES and the incidence of respiratory disease.…”
Section: Discussionmentioning
confidence: 87%
“…Probably, it is implied by different definitions of SES and its various research areas which are taken into account in studies. Some papers indicate that a high percentage of children with asthma come from families with a low SES, while others do not find relationships between SES and the incidence of asthma and allergy [6,7]. In the study by Poyser et al it was found that asthma is a disease of affluent individuals, while Hancox et al did not observe any relationship between parents' income and the incidence of asthma in a group of 13-and 15-year-olds [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As diferenças de prevalência da asma quando considerados diferentes níveis socioeconômi-cos mostram resultados controversos 28,29 . No Brasil, alguns estudos encontraram prevalência de asma maior em adolescentes de baixo nível socioeconômico 30,31 .…”
Section: Discussionunclassified
“…Shankardass et al (2007) found that census-derived estimates of community-level socioeconomic status, including male unemployment, household income, low educational attainment, and poverty, were consistently inversely associated with prevalent childhood asthma controlling for individual level measures of social economic status (SES) [36]. Using health care utilization records and census tract demographic data from Alameda County, CA, Roberts et al (2008) observed that high poverty communities tended to have higher rates of outpatient emergency care for asthma, as well as lower rates of indicators for quality primary care for asthma [37].…”
Section: Discussionmentioning
confidence: 99%